Pengembangan Rancangan Pameran Virtual Berbasis Media Augmented Reality - Damara, Muhamad Albir; Kustiono, Kustiono; Sukirman, Sukirman (Indonesian Journal of Curriculum and Educational Technology Studies, 2018)
Augmented reality (AR) could be a new technology to address the exhibition event become more interesting, secure and its product could be easily renewable for educational purposes. This article describes the development process of AR media and fnd out it feasibility as a learning tool for 3D animation lecture at higher education level. This research employing Research and Development (R & D) model and adapted 10 stages of R & D model from Sugiyono (2013) into four primary steps, i.e. (1) analysis, (2) design, (3) development and (4) testing the product. The feasibility of the product has been tested by media expert and showed a very good result with average score at 95%, the testing product for student also gained the same result with average score at 81%. The result of this research proved that AR was feasible as a learning media for 3D animation lecture and therefore it has a potential to be used for another context for educational purposes. Abstrak Media augmented reality (AR) dapat dipergunakan sebagai teknologi baru dalam penyelenggaraan pameran secara virtual sehingga produk yang dipamerkan akan terpelihara dan dapat diperbarui. Artikel ini menggambarkan proses pengembangan media AR dan mengetahui kelayakannya sebagai media penunjang pembelajaran mata kuliah Animasi 3D. Penelitian ini menggunakan model research and development yang mengadaptasi 10 tahap pengembangan sugiyono dan disederhanakan menjadi 4 tahap utama, yaitu (1) analysis, (2) desain, (3) pengembangan produk, dan (4) ujicoba produk. Hasil uji kelayakan yang dilakukan oleh ahli media diperoleh rata-rata persentase 95% dengan kriteria sangat baik. Selain itu hasil ujicoba kepada mahasiswa didapatkan perolehan rata-rata persentase 81% dan masuk dalam kategori sangat baik. Hasl penelitian ini menunjukkan bahwa AR memang terbukti layak digunakan sebagai media pembelajaran dalam mata kuliah Animasi 3D dan oleh karenanya potensial juga digunakan untuk mata kuliah dan pembelajaran lain. Kewords:  Augmented reality; educational technology; exibhition; research & development; virtual media